2019
DOI: 10.31698/ped.46022019004
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización clínica y demográfica de la hospitalización psiquiátrica infantojuvenil en un hospital general

Abstract: Introducción: Se implementan actualmente nuevos modelos de hospitalización psiquiátrica infantojuvenil, para hacer frente a la creciente demanda de recursos de atención psiquiátrica intensiva requeridos por esta población. Objetivo: Identificar las características clínicas y demográficas de los niños y adolescentes con diagnóstico psiquiátrico hospitalizados en Salas de Pediatría de un Hospital General Pediátrico. Metodología: Estudio descriptivo, retrospectivo de corte transversal, en base a historias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Detailed findings of the included studies are collated in tables 1–4. Eighteen studies addressed trends and/or numbers/proportions of admissions,3 4 6–8 18–30 12 provided data about HCP views/experiences,4 31–41 two provided data about CYP views/experiences37 42 and four aimed at improving the care during admissions 6 40 43 44…”
Section: Resultsmentioning
confidence: 99%
“…Detailed findings of the included studies are collated in tables 1–4. Eighteen studies addressed trends and/or numbers/proportions of admissions,3 4 6–8 18–30 12 provided data about HCP views/experiences,4 31–41 two provided data about CYP views/experiences37 42 and four aimed at improving the care during admissions 6 40 43 44…”
Section: Resultsmentioning
confidence: 99%
“…Ibeziako et al (7) reported 3799 paediatric MH admissions to the ED and inpatient units at a paediatric hospital from March 2019 – February 2021. Duarte and Zelaya (26) reported 180 admissions of patients with psychiatric diagnoses (January-August 2015); 74.4% required admission to the paediatric ward or hospital inter-consultation because of psychiatric pathology or primary psychiatric disorders. Wallis (28) reported 111 emergency admissions (83 patients) of CYP with MH needs to the paediatric ward between August 2017 and July 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed findings of the included studies are collated in Tables 1-4. Eighteen studies addressed trends and or numbers/proportions of admissions (3,4,(6)(7)(8)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), 12 provided data about HCPs views/experiences (4,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), two provided data about CYP views/experiences (37,42) and four aimed at improving the care during admissions (6,40,43,44).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations